2003
DOI: 10.1021/ie0207616
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a Porous Reactor for Supercritical Water Oxidation by a Residence Time Distribution Study

Abstract: Supercritical water oxidation (SCWO) performances are limited by salt precipitation and corrosion when it comes to treating real wastes. A porous reactor has been developed to overcome these problems. It consists of a concentric double-wall reactor in which the corrosive reactants are maintained inside an alumina porous tube, whereas pressure resistance is ensured by a stainless steel external vessel. Hydrodynamics in the reactor is thought to be rather complex. Thus, a residence time distribution study was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Most commercial and industrial applications require that engineering designs and materials overcome corrosion and plugging problems and that systems operate on a continuous duty cycle (Azadi et al, 2011;Elliott, 2008;Guo et al, 2007). Some common, SCW-reactor considerations are presented here, while extensive and detailed reviews can be found elsewhere (Bermejo et al, 2005a(Bermejo et al, , 2005b(Bermejo et al, , 2009Calzavara et al, 2004;Fauvel et al, 2003Fauvel et al, , 2005Lieball et al, 2001;Machida et al, 2011;Marrone & Hong, 2009;Mitton et al, 2000;Peter, 2004;Tan et al, 2011;Veriansyah et al, 2009;Wellig et al, 2005;Yoshida & Matsumura, 2009). …”
Section: Reactor Kinetics and Design Considerationsmentioning
confidence: 99%
“…Most commercial and industrial applications require that engineering designs and materials overcome corrosion and plugging problems and that systems operate on a continuous duty cycle (Azadi et al, 2011;Elliott, 2008;Guo et al, 2007). Some common, SCW-reactor considerations are presented here, while extensive and detailed reviews can be found elsewhere (Bermejo et al, 2005a(Bermejo et al, , 2005b(Bermejo et al, , 2009Calzavara et al, 2004;Fauvel et al, 2003Fauvel et al, , 2005Lieball et al, 2001;Machida et al, 2011;Marrone & Hong, 2009;Mitton et al, 2000;Peter, 2004;Tan et al, 2011;Veriansyah et al, 2009;Wellig et al, 2005;Yoshida & Matsumura, 2009). …”
Section: Reactor Kinetics and Design Considerationsmentioning
confidence: 99%
“…Reports [57][58][59], Crooker et al [60] (and literature cited in Ref. [60]), Abeln et al [61,62], Fauvel et al [63]), yet the use of a separate hydrothermal flame as an internal heat source is novel in SCWO reactors. Table 1.…”
Section: Fundamentals Of the Novel Transpiring-wall Reactormentioning
confidence: 99%
“…However, little information is available about RTD curves in reactors working at supercritical conditions, so far. Fauvel et al [11] estimated that such a study is difficult to perform in such conditions because of the compressibility of near critical and supercritical fluids. They concluded that this is possibly the reason of the lack of reported RTD experiments in supercritical fluids.…”
Section: Introductionmentioning
confidence: 99%
“…RTD theory requires a constant-volume flow rate in the reactor and that is difficult to achieve when dealing with compressible gases. In addition to this, in some cases like supercritical water, the extreme pressure and temperature conditions (over 22.1 MPa and 374.1 • C) causes damage to most of the detectors and cannot be easily measured directly [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation